Risk of Beta: Evidences from prospect theory - roohollah farhadi; علی ثقفی; محمد تقی تقوی فرد (مطالعات تجربی حسابداری مالی, 2015)
According to Prospect Theory, Investors have different behaviors in the profit and loss situations and indeed their trading behavior is different in bull and bear markets. This study uses quantile regression model (in different quartiles) and OLS model to estimate beta of 180 firms. Results showed that first, equity total risk (standard deviation) increase in Upper quartile and second, stocks beta changes in different quartiles and by moving from quartile 0.25 to quartile0.75, systematic risk (beta) increases significantly. Linear regression model and Quantile regression model show also that unexpected variance can explain excess return at least similar to expected variance. The results can also be interpreted with both Insight of standard finance and insight of behavioral finance. In standard finance area, risk-return positive relation that exists in upper quintiles is consistent with long run growth of economy. Moreover, negative relation between return and risk in lower quintiles imply more uncertainty and as a result causing stock returns to fall. In behavioral finance area, regime-dependent behavior of slope coefficients is consistent with prediction of Prospect theory of investor’s behaviors around the reference point.